2014
DOI: 10.1007/7651_2014_116
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Expansion of Mesenchymal Stromal/Stem Cells from Umbilical Cord Under Chemically Defined Conditions

Abstract: From a perspective of manufacturer, procurement of bone marrow aspirates for isolation of mesenchymal stromal/stem cells (MSC) is challenging. The MSC isolated from adult donors have lower proliferation capacity than the cells isolated form young donors of pediatric age. To obtain more MSC from young healthy donors for allogeneic therapy on multiple patients, umbilical cord (UC) seems to be the best alternative. Here, we describe an easy, cost-effective and reproducible protocol of isolation of the MSC from Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 12 publications
0
9
1
Order By: Relevance
“…Issues such as source of donor tissue, donor age, environmental background, and isolation methods have been described to impact upon the overall quality of these cells (Badraiq et al 2014;Mori et al 2014;Swamynathan et al 2014). However, individual variability is still an unanswered issue, which we sought to address studying UC-MSCs.…”
Section: Discussionmentioning
confidence: 98%
“…Issues such as source of donor tissue, donor age, environmental background, and isolation methods have been described to impact upon the overall quality of these cells (Badraiq et al 2014;Mori et al 2014;Swamynathan et al 2014). However, individual variability is still an unanswered issue, which we sought to address studying UC-MSCs.…”
Section: Discussionmentioning
confidence: 98%
“…Previous study has showed that MSCs could not be isolated and expanded in StemPro MSC SFM medium, mTeSR or TheraPEAKTM MSCGM‐CDTM alone, and the addition of human AB serum is needed for the initial isolation . Moreover, high cell seeding densities are needed for MSCs subculture, and lesser density could slow cell proliferation . Some studies have also reported that the isolation, expansion, phenotype and differentiation potential of MSCs are not well supported in MesenCult‐XF .…”
Section: Introductionmentioning
confidence: 99%
“…Collection of the samples was described previously 49 . Briefly, following informed consent, for this study we recruited seven healthy obese pregnant women with BMI ≥ 30 and seven healthy non-obese with BMI between 21 and 25 at the gestational age of 37 weeks (Figure S1 ).…”
Section: Methodsmentioning
confidence: 99%
“…The derivation of MSCs from UC explants and standard cell culture were described in detail previously 1 , 49 . Briefly, the 5–10 mm 2 explants were cultured in DMEM supplemented with 10% fetal calf serum (Hyclone) at 37 °C, 5% CO 2 , 5% O 2 .…”
Section: Methodsmentioning
confidence: 99%